2006
DOI: 10.1074/jbc.m602496200
|View full text |Cite
|
Sign up to set email alerts
|

Homer 1 Mediates Store- and Inositol 1,4,5-Trisphosphate Receptor-dependent Translocation and Retrieval of TRPC3 to the Plasma Membrane

Abstract: Ca2ϩ influx is a critical component of the receptor-evoked Ca 2ϩ signal and plays a role in many physiological functions (1). The best described form of Ca 2ϩ influx is mediated by the store-operated Ca 2ϩ channels (SOCs), 3 which are activated by agonist-dependent or agonist-independent depletion of Ca 2ϩ stored in the ER (1). The molecular identity of the SOCs and I crac is still not known with certainty, although recent work points to ORAI1/CRACM1/olf186-F as a potential I crac (2-5). However, accumulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
102
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 53 publications
7
102
0
Order By: Relevance
“…In addition to the mGluRs, many Ca 2+ signaling proteins express Homer ligands and bind Homer. Among them are the scaffolding protein Shank [8], PLCβ [16,17], IP 3 receptors (IP 3 Rs) [15,18], TRPC channels [15,18], ryanodine receptors (RyRs) [19][20][21][22] and selective L-type Ca 2+ channel isoforms [23][24][25].…”
Section: Homers Localization and Binding To Ca 2+ Signaling Proteinsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to the mGluRs, many Ca 2+ signaling proteins express Homer ligands and bind Homer. Among them are the scaffolding protein Shank [8], PLCβ [16,17], IP 3 receptors (IP 3 Rs) [15,18], TRPC channels [15,18], ryanodine receptors (RyRs) [19][20][21][22] and selective L-type Ca 2+ channel isoforms [23][24][25].…”
Section: Homers Localization and Binding To Ca 2+ Signaling Proteinsmentioning
confidence: 99%
“…It should be possible to resolve this issue with the availability of mice from which single and combination of the Homers are deleted. The knockout mice were instrumental in discovering the acceleration of RGS proteins GAP activity by Homer2 [30] and the role of Homer1 in conformational coupling and excitation-contraction coupling (see below and [15,18]). These studies showed that H1a facilitates, while H1b/c impedes Ca 2+ signaling by regulating communication between Ca 2+ release channels at the ER/SR and Ca 2+ influx channels at the plasma membrane.…”
Section: Homer1 In Neuronal Ca 2+ Signalingmentioning
confidence: 99%
See 3 more Smart Citations